Ceci N’Est Pas Une Publication: The Art of AI-Generated Research Papers - Zolezzi, Daniele (International Journal of Emerging Technologies in Learning (iJET), 2024)
The advent of Generative Artificial Intelligence (genAI) has significantly reshaped the educational landscape, heralding new prospects and concurrently introducing complex challenges. Mirroring the essence of René Magritte’s iconic artwork “Ceci n’est pas une pipe”, where the depiction of a pipe is not actually a pipe, this publication is not a publication, at least not from the beginning. This article acts as a case study, showcasing the ability to generate coherent and pertinent AI-created content, while also drawing attention to its limitations in depth and diversity. Moreover, it underscores the facility with which such content can be produced. The paper culminates by examining the role of AI-generated content within the academic sphere, particularly highlighting the complexities involved in distinguishing AI-produced material from human-authored text.